Nupharidine enhances Aggregatibacter actinomycetemcomitans clearance by priming neutrophils and augmenting their effector functions. (18th December 2018) - Levy, Dan Henry; Chapple, Iain L. C.; Shapira, Lior; Golan‐Goldhirsh, Avi; Gopas, Jacob; Polak, David
Abstract: Objectives: Nupharidine (6, 6′‐Dihydroxythiobinupharidine), purified from the aquatic plant Nuphar lutea leaves (Water lily) prompts antimicrobial activity of immune cells. The aim of the study was to test the effect of Nupharidine on neutrophil function against Aggregatibacter actinomycetemcomitans, JP2 clone (Aa‐JP2). Methods: Neutrophils derived from the human cell line HL60 and human peripheral blood derived from aggressive periodontitis and periodontally healthy subjects were incubated with Nupharidine or vehicle and inoculated with JP2. Bacterial survival was tested using viable counts on blood agar (CFU's). Neutrophils' necrosis/apoptosis, reactive oxygen species (ROS) production, phagocytosis and neutrophil extracellular traps (NET) production following infection were tested, as well as markers of neutrophil priming. Results: Nupharidine had no direct bactericidal effect on JP2, but it enhanced Aa‐JP2 clearance by neutrophils. Nupharidine enhanced neutrophil phagocytosis, ROS production and NET formation during JP2 infection. Furthermore, Nupharidine enhanced the expression of certain markers of neutrophils priming, specifically iCAM1, DECTIN‐2 and intracellular IL‐1β. Conclusion: Nupharidine was shown to promote neutrophil effector bactericidal functions, boosting Aa‐JP2 clearance. The results point to the potential of Nupharidine as an adjunctive agent in the treatment of Aa‐JP2 periodontitis, but this should be tested initially using pre‐clinical and clinical studies.